(untitled) (Anais do Salão Inovação, Ensino, Pesquisa e Extensão, 2023)
The engagement in English classes is very important to increase students interest in the language. However, it is a tough task because many people may find it difficult to develop their work in a public school due to the great variety of challenges. As an illustration of this: the big number of scholars, the lack of technological devices to use in class, the indifference of some students about learning English and the reduced frequency of classes during the week. For this reason, this paper aims to discuss about the students resistance to learning and speaking English during the English classes in public schools, situated in Bagé and about the strategies that were used in the classroom in order to catch the students attention and motivate them, from the perspective of two student-teachers of Additional Languages. And also, how the motivation of a teacher can encourage the students to participate, get engaged in all the activities and get the most knowledge they can in a class. Primarily, the practicum classes are taught in order to prepare students to be teachers after graduating, although we have been studying a wide range of methodologies to use in class, it is difficult to apply all these methods when you assume a class that you do not know the students and the only contact you had with them was the observation. Moreover, the first task was to find a school that could accept the student-teachers for the accomplishment of the English practicum. So, each student-teacher found a school as the first challenge. Secondly, 4 hours of classes were observed and after this, it was necessary to have a break of two weeks to prepare the class plans. In sequence, it was used some specific contents and themes in order to call the students attention, such as the usage of series, social media, movies, celebrities and matters that are from their daily lives, routine and hobbies. The first classes were the most frightening and difficult to deal with. The students demonstrated to be curious about the teachers and about what they would do there. All the student groups were quite energetic and wild, always screaming and getting up from their chairs, with lots of resistance to speak and to interact with the teachers during the main activities. After some classes, It was realized that the students did not like to speak English in the classroom, which was surprising, because the plans that were made were focused on speaking activities and the students were not as well-behaved as they seemed to be. For these reasons, the next classes were prepared focusing on writing activities, but never leaving the other skills behind, and it was adopted as a better way to conduct the classes. As a result, the following class plans were prepared taking into consideration the perception that we acquired during the classes. The perception of the teachers was that the students demonstrated to be more motivated to study the language and get encouraged to take risks during the classes embracing making mistakes as a fundamental part of the process of learning by interacting more in classes and doing the proposing activities. Furthermore, the scholars that already liked the theme of the classes started to interact more when the focus of the activities was changed, acquiring an aspect more written than oral. Although the students still would had to speak English in the classroom. Their participation increased because they already had a script to speak. To conclude, all the classes were a different challenge but they shared one thing in common, the motivation that us, as teachers, implied to the students, because motivation is key for the success of the human being, so the students must be motivated to learn too. Showing the students that they are capable of learning and able to do what they want is a key role for the teacher. It was possible to find strategies to encourage the students to be more participative during the activities, and this made us feel really proud of ourselves.